Coastal ecosystem inventory with characterization and identification of plastic contamination and additives from aquaculture materials. (June 2021) - Bringer, Arno; Le Floch, Stéphane; Kerstan, Andreas; Thomas, Hélène
Abstract: In the early 1970s, studies of marine litter first appeared in the scientific literature. Fifty years later, knowledge of several coastal areas of the Atlantic, the driving forces of oyster farmers and aquaculture, is lacking. This work documents a pilot study on an Atlantic coastal area (France). This study aims to (i) characterize the abundance of macroplastics related to aquaculture tools; (ii) microplastics present in beach sediments and (iii) characterization of pollutants present on aquaculture plastics collected. First, it was observed that 70% of the plastics collected on the beach were characteristic of aquaculture materials. In sediments, MPs most found were Polyamide between 10 and 20 μm, with a total MP concentration of 397–457 MPs.kg −1 . Pipes collectors (PVC), frequently used in aquaculture, have been shown to have concentrations of dimethylphthalates and naphthalene. Waste management and support policies can then base their actions on such studies, in order to improve their knowledge. Graphical abstract: Unlabelled Image Highlights: Significant presence of aquaculture macroplastics on the beach studied Microplastics found in surface and semi-depth sediments, between 397 and 457 MPs/kg Polyamide microplastics of 10–20 μm found mainly in beach sediments Characterization of additives and PAHs on aquaculture plastics Detection of dimetylphthalate and naphthalene on aquaculture PVC materials